ROLE OF INFORMATION AND COMMUNICATION TECHNOLOGIES IN THE AGROINDUSTRIAL COMPLEX - Kholmurzayeva Nigora Abdimurotovna (Galaxy International Interdisciplinary Research Journal, 2021)
The article examines the role of information and communication technologies in the agro-industrial complex. The world and Uzbek experience of using ICT in the agro-industrial complex is presented, the main problems of introducing ICT are stated.